Self-rostering and psychosocial work factors – A mixed methods intervention study. (March 2015) - Hansen, Åse Marie; Nabe-Nielsen, Kirsten; Albertsen, Karen; Hogh, Annie; Lund, Henrik; Hvid, Helge; Garde, Anne Helene
Abstract: This study aims at 1) examining the effect of self-rostering on emotional demands, quantitative demands, work pace, influence, social community at work, social support from leaders and colleagues, job satisfaction, and negative acts, 2) examining whether this effect was mediated through increased influence on the scheduling of working hours, and interpreting the results in light of the different implementation processes that emerged in the study and by including qualitative data. We conducted a 12 months follow-up, quasi-experimental study of self-rostering among 28 workplaces out of which 14 served as reference workplaces. We also interviewed 26 employees and 14 managers about their expectations of introducing self-rostering. In the present study implementation of self-rostering had a positive effect on job demands and the social environment of the workplace, especially if the intervention does not comprise drastic changes of the organisation of the employees' work and private life. Highlights: Implementing self-rostering has a potential to improve the psychosocial factors at work. There were large differences of implementing self-rostering on the effects of psychosocial factors at work. The effect on psychosocial factor seemed to be dependent on the aim and content of intervention.